Rapid sizing of individual fluorescently stained DNA fragments by flow cytometry. - Goodwin, P M (1993)
Large, fluorescently stained restriction fragments of lambda phage DNA are sized by passing individual fragments through a focused continuous wave laser beam in an ultrasensitive flow cytometer at a rate of 60 fragments per second. The size of the fluorescence burst emitted by each stained DNA fragment, as it passes through the laser beam, is measured in one millisecond. One hundred sixty four seconds of fluorescence burst data allow linear sizing of DNA with an accuracy of better than two percent over a range of 10 to 50 kbp. This corresponds to analyzing less than 1 pg of DNA. Sizing of DNA fragments by this approach is much faster, requires much less DNA, and can potentially analyze large fragments with better resolution and accuracy than with gel-based electrophoresis.